Mekanisme Penghimpunan Wakaf Uang Pada Koperasi Simpan Pinjam dan Pembiayaan Syariah Baitul Maal Wattamwil - Nanang Sobarna; Gina Ayunisa Rahmani (Coopetition : Jurnal Ilmiah Manajemen, 2023)
The Baitul Maal Wattamwil (BMT) Al-Amanah Situraja Sumedang Savings and Loans and Sharia Financing Cooperative (KSPPS) is a Sharia Cooperative that has the authority to collect zakat, infaq, shadaqah and waqf funds, including cash waqf. In order to finance and carry out empowerment through cash waqf, KSPPS BMT Al-Amanah Situraja Sumedang is actively engaged in collecting cash waqf so that the cash waqf empowerment program is in order to achieve prosperity for members and the community. The purpose of this study is to find out the mechanism for collecting cash waqf KSPPS BMT Al-Amanah Situraja Sumedang. The research method used is descriptive analysis with a qualitative approach through observation of the object studied, as well as interviews with informants to be able to describe the collection of cash waqf at KSPPS BMT Al-Amanah Situraja Sumedang. Based on the results of an analysis of the mechanism for collecting cash waqf funds at KSPPS BMT Al-Amanah Situraja Sumedang, this was carried out by conducting intensive outreach to members and the public, both directly and through social media. Through this program, waqif candidates are interested in making cash waqf at KSPPS BMT Al-Amanah Situraja Sumedang with a cash waqf payment system or by installments through various installments.